Viability and effects on bacterial proteins by oral rinses with hypochlorous acid as active ingredient (2015)
This study investigated the effect of hypochlorous acid (HOCl) rinses and chlorhexidine (CHX) on the bacterial viability of S. mutans, A. israelii, P. gingivalis, A. actinomycetemcomitans, E. corrodens, C. rectus, K. oxytoca, K. pneumoniae and E. cloacae. The percentage of live bacteria was tested by fluorescence method using Live/Dead kit(r) and BacLight (Molecular Probes(r)) and compared between groups by the Kruskal-Wallis and U Mann-Whitney tests with Bonferroni correction (p value<0.012). The effect of HOCl and CHX on total proteins of P. gingivalis and S. mutans was determined by SDS-PAGE. CHX showed a higher efficacy than HOCl against S. mutans, A. israelii, E. corrodens and E. cloacae (p<0.001) while HOCl was more effective than CHX against P. gingivalis, A. actinomycetemcomitans, C. rectus and K. oxytoca (p=0.001). CHX and HOCl had similar efficacy against K. pneumoniae. Proteins of P. gingivalis and S. mutans were affected similarly by HOCl and CHX. HOCl reduced the bacterial viability especially in periodontopathic bacteria, which may support its use in the control of subgingival biofilm in periodontal patients.